PREVENTION OF CARIES DEVELOPMENT DURING ORTHODONTIC TREATMENT (World Bulletin of Social Sciences, 2021)
The main object of this article is to improve the diagnosis and prevention of the development of caries and its complications during orthodontic treatment.